Numerical investigation on the performance of Wells turbine with non-uniform tip clearance for wave energy conversion - Zahari, Taha; Sugiyono, .; T. M. Y. S., Tuan Ya; Sawada, Tatsuo (Elsevier, 2011)
The performance of a Wells turbine with various non-uniform tip clearances was investigated using computational fluid dynamics (CFD). The investigation was performed on numerical models of a NACA0020 blade profile under steady flow conditions. The performance of turbines with uniform and non-uniform tip clearances was compared. The results were also compared with experimental results in literature. It was shown that the performance of turbine with non-uniform tip clearance is similar with that of turbine with uniform one in terms of torque coefficient, input power coefficient, and efficiency. However, the turbine with non-uniform tip clearance seems to have a preferable overall performance. An investigation on the flow-field around the turbine blade was performed in order to explain the phenomena.